A study on analysis of caesarean section indications using Robson’s ten group classification system - Arora, Mamta; Chandanan, Ani; Kotwal, Ankush Singh; Garhwal, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Over the past decades, there has been a steady rise in the rate of caesarean delivery. Although not well understood, multiple factors have contributed to this uptrend. The goal of cesarean delivery is to avoid the complications that might develop after vaginal delivery. However, this major surgery is not without significant impact on maternal and fetal outcomes. Maternal complications include the increased risk of post-partum hemorrhage, risk of hysterectomy, infection and deep venous thrombosis besides longer hospital stay. Methods: This was retrospective observational study done in the department obstetrics and gynecology at T. S. Misra medical College for a duration of 18 months from December 2021 to May 2023. It included all patients who underwent caesarean section. Results: In our study maximum patients were in group 10(30.2%) according to Robsons classification followed by group 5 (20.9%). Conclusions: In conclusion, the rate of caesarean delivery is trending up and this has contributed to significant medical, social and financial impacts in the involved families. The most common indication for CS is previous CS. Therefore, the rate of CS can be controlled if CS is done in primigravidae with the genuine indication.